Numerical Simulation of Heat Removal from a Window Slab Partition of a Radiative Coil Coating Oven - Rodrigo J. F. Neno; Beatriz S. Dias; Jorge E. P. Navalho; José C. F. Pereira (Energies, 2022)
In this work, fluid flow and heat transfer performance of a radiative coil coating oven is numerically investigated. In the coil coating oven concept under consideration, porous radiant burners provide the required energy to evaporate the volatile species (solvents) from the applied coating and to promote curing reactions. To avoid the mixing between burners flue gas (with a non-negligible oxygen content) and evaporated (combustible) solvents in the oven (which could lead to a catastrophic oven failure), a semi-transparent window in between both atmospheres is applied. To ensure the window thermal stability during the oven operation, window cooling by wall jets is considered. Different turbulence models were compared against available wall jet heat transfer correlations to select the most suitable for three-dimensional (3D) numerical simulations. Convective heat transfer correlations purposefully developed were embedded in a one-dimensional (1D) window energy model for fast performance characterization, analysing the most influencing parameters—window radiative properties, thickness, inlet temperature and velocity of wall jets, and cooling strategy. The 1D window thermal performance is compared with literature and 3D results considering the full coil coating oven, providing satisfactory confidence on the developed strategy. The 1D model is used for an optimisation study to find the minimum energy consumption while ensuring the safety requirements (maximum window temperature and thermal gradient) are met.